Efficient and Stable Photocatalytic Hydrogen Evolution Activity of Multi-Heterojunction Composite Photocatalysts: CdS and NiS2 Co-modified NaNbO3 Nanocubes - Xu, Jingjing; Zhu, Jiawei; Niu, Junfeng; Chen, Mindong; Yue, Junpeng (Frontiers in Chemistry, 2020)
In this study, a NaNbO3/CdS/NiS2 ternary composite photocatalyst containing no precious metals was successfully prepared by simple hydrothermal method. The prepared ternary photocatalyst has a significant improvement in photocatalytic performance of hydrogen production from water splitting under visible light irradiation. The best sample NCN40% hydrogen production rate is 4.698 mmol g-1 h-1, which is about 24.7 times as that of pure CdS sample. In addition, the stability of the composite catalyst in the long-term photocatalytic hydrogen production cycle is also improved. The reason for the enhanced hydrogen production performance may be the optimization of the microstructure of the catalyst and the reduction of photogenerated electron-hole recombination. The construction of multi-heterojunctions (NaNbO3-CdS, CdS-NiS2, NaNbO3-NiS2) help to reduce the recombination of carriers. Furthermore, the in-situ formed NiS2 nanoparticles can be served as active sites for hydrogen evolution. All of these factors induced to the improved photocatalytic activity of the as-prepared ternary photocatalyst.